PENERAPAN PROGRAM MARKET DAY DALAM MENSTIMULASI PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI DI RA AN-NAMIROH KISARAN: IMPLEMENTATION OF MARKET DAY PROGRAM TO STIMULATION EARLY CHILD SOCIAL EMOTIONAL DEVELOPMENT IN RA AN-NAMIROH KISAR - RISMAYANI; DEA PUTRI JELITA; MARTINI; SITI MAHPUDZOH SRG; KHADIJAH (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to determine the results and process of implementing market day in stimulating social emotional development of early childhood in the B RA An-Namiroh Kisaran group. This research is a type of descriptive qualitative research that describes the reality in the field at the time the research was conducted. The data collected was analyzed narratively, namely collecting descriptions of events or incidents and then compiling them into stories. The subjects of this study were group B children of An-Namiroh Kisaran Kindergarten. Data collection techniques in this study were carried out by interviews, observation, and documentation. The results showed that the market day activities carried out at An - Namiroh Kindergarten range for group B children aged 5-6 years can be seen from the attainment of indicators of social emotional abilities of children aged 5-6 years, namely from a. Self-awareness, b. Sense of responsibility, c. Prosocial behavior.